(untitled) (UUM Journal of Legal Studies, 2025)
This research aims to answer the following questions: First, what is the legal certainty of copyright protection in the field of scientific works in the declarative system in Indonesia and Malaysia? Second, how can rights holders prove if a dispute occurs due to copyright infringement in science? Based on copyright law, the basis for the emergence of rights and legal protection is not based on registration. However, it is based on the birth of copyrighted work, realised in a tangible form known as a declarative system. For example, creative works in science have been produced into books that may be read and used as reading material. In such a system, issues may arise concerning the certainty of legal protection and proof in the event of a disagreement. This research employs a normative approach, examining key legal documents such as statutes, rules and case decisions. According to the findings of the study, the declarative system can nevertheless provide clarity and legal protection to copyright proprietors or inventors. At the same time, proof can be done with testimony of witnesses or written evidence, but the proof will be more straightforward if the right to work is registered by obtaining a copyright registration certificate. A copyright registration certificate will provide more certainty of rights and legal protection, and is easy to prove.